Recent Study of Screening Echocardiography in Asymptomatic Pregnant Women - Gomathi, T.; Thendral, V. (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Introduction: Heart disease is more prevalent in women of childbearing age. In unbooked and newly diagnosed heart disease complicating pregnancy, heart disease is the leading cause of maternal mortality and morbidity. The signs and symptoms of pregnancy may confuse with the signs and symptoms of heart disease. Over the last decade, the utility of echocardiography as an imaging technique has increased significantly. The echocardiogram is the gold standard and definite diagnostic tool for diagnosing heart disease. Our goal is to use screening echocardiography to detect heart disease in asymptomatic pregnant women. Materials and Methods: This study included 300 pregnant women in all trimesters of their pregnancy. The study period at Government Kilpauk Medical College runs from October 2016 to January 2017. Those with a history of heart disease were barred from participating. All patients underwent conventional M mode, 2D, and Doppler echocardiography. Results: Out of 300 study population 65% (n-195), 23% (n-69)and 12% (n- 36) patients were in first, second and third trimester respectively. We found that 6.3% (n-19) of patients had either congenital or acquired heart disease. Among this, acquired heart disease burden is about 63% (n-12) and congenital heart disease is 37% (n-7). In congenital heart disease, Mitral valve prolapse 42.8% (n-3) atrial septal defect 28.5% (n-2), valvular pulmonary stenosis 14.2% (n-1) and coarctation of aorta 14.2% (n-1) were diagnosed. In acquired heart disease rheumatic heart disease found in all patients (100% (n-12). Among the Rheumatic etiology isolated stenotic lesion in 50% (n-6,) isolated regurgitant lesion in 33.3% (n-4) and combined lesion in 16.6% (n-2) were identified in the study population. Conclusion: According to our findings, screening echocardiography will undoubtedly aid in the detection of heart disease and the reduction of heart disease-related mortality. Even in the absence of cardiopulmonary symptoms, this will justify routine cardiac evaluation.